2015
DOI: 10.1186/s12906-015-0660-1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant flavonoids from the leaves of Oncoba spinosa Forssk. (Salicaceae)

Abstract: BackgroundNaturally occurring flavonoids have been reported to possess various pharmacological properties. The aim of this study was to evaluate the antimicrobial and antioxidant activities of the MeOH extract and flavonoids from the leaves of Oncoba spinosa, a plant used for the treatment of syphilis, wounds and sexual impotence.MethodsThe plant extract was prepared by maceration in methanol and sequentially fractionated by column chromatography. The structures of isolated compounds were elucidated on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 24 publications
2
50
0
Order By: Relevance
“…The antioxidant capacity of the tested extracts may be due to the hydrogendonating ability of phenols and flavonoids present in those extracts. Similarly, previous studies have reported that phenolic compounds contribute significantly to the antioxidant activity of medicinal plants (39,48). The compounds that had the most potent DPPH…”
Section: Antioxidant Activitymentioning
confidence: 60%
See 2 more Smart Citations
“…The antioxidant capacity of the tested extracts may be due to the hydrogendonating ability of phenols and flavonoids present in those extracts. Similarly, previous studies have reported that phenolic compounds contribute significantly to the antioxidant activity of medicinal plants (39,48). The compounds that had the most potent DPPH…”
Section: Antioxidant Activitymentioning
confidence: 60%
“…All of the compounds that were found to be active in the present study are members of the triterpenoid, flavonoid, and phenolic acid groups. Although triterpenoid, flavonoid, and phenolic acid compounds have been reported to possess antibacterial activity (39,44), no study has reported the activity of compounds 3 and 6-10 on the types of MDR pathogenic bacterial strains used in the present study.…”
Section: Antibacterial Activitymentioning
confidence: 85%
See 1 more Smart Citation
“…The results of MIC and MBC showed that the MIC values obtained were four times equal to or lesser than the MBCs on the corresponding (sensitive) bacteria, suggesting the bactericidal effects of the concerned samples. 27,28,29 This is interesting in view of the perspective of developing new antibacterial drugs from endophytic fungus. The present study showed antibacterial activity of penialidin A-C (1-3), citromycetin (4), p-hydroxyphenylglyoxalaldoxime (5) and brefelfin A (6) from Penicillium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Many plant derived compounds including phenols, quinones, terpenoids, flavones have been reported to possess antibacterial activity. (Djouossi et al, 2015;Cabral et al, 2015). …”
Section: Discussionmentioning
confidence: 99%